Experimental investigation on heat transfer behavior in a tight 19 rod bundle cooled with supercritical R134a. (May 2018) - Chen, Jiayue; Gu, Hanyang; Xiong, Zhenqin; Liu, Da
Highlights: Heat transfer experiments on a tight 19 rod bundle have been performed. The cause of circumferentially non-uniform wall temperature are discussed. Parametric effects on circumferential non-uniformity are studied. Abstract: The strong non-uniform distributions of circumferential wall temperature and heat transfer coefficient will exist in tight-lattice rod bundles. However, there is still a lack of understanding and only a few experimental data are available. In this paper, experimental investigations are performed on circumferential heat transfer behavior in a tight hexagonal 19 rod bundle using supercritical R134a as working fluid. The rod surface temperatures at various circumferential positions along the axial flow direction are measured. A defined local hydraulic diameter is introduced to represent the heterogeneity of channels in the tight bundle. The circumferentially non-uniform distribution of wall temperature is found to be strongly related to the variation of the local hydraulic diameter. In normal heat transfer pattern, the circumferential temperature gradient is large especially in the region far away the pseudo critical point, but becomes small near the pseudo critical point due to a strong enhancement of heat transfer coefficient. Parametric effects of pressure, mass flux and heat flux on circumferential non-uniformity of wall temperature inside the rod bundle are also analyzed.